2018
DOI: 10.1111/obr.12787
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for novel intermittent dieting strategies to attenuate adaptive responses to energy restriction

Abstract: Eating patterns involving intermittent energy restriction (IER) include 'intermittent fasting' where energy intake is severely restricted for several 'fasting' days per week, with 'refeeding' days (involving greater energy intake than during fasting days) at other times. Intermittent fasting does not improve weight loss compared to continuous energy restriction (CER), where energy intake is restricted every day. We hypothesize that weight loss from IER could be improved if refeeding phases involved restoration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 63 publications
1
23
0
1
Order By: Relevance
“…Some have postulated that achieving energy balance (or the absence of energy restriction) appears to be important in order to attenuate the effects of the adaptive responses to energy restriction [1,39]. A number of investigations have reported that participants consume less than their weight maintenance energy requirements during refeeding days, and subsequently are in varying degrees of energy restriction for the duration of the intervention [1,6,40,41]. In a comprehensive review on this topic, Sainsbury and colleagues [1] summarized all known randomized controlled trials in overweight/obese adults in which energy balance was intermittently restored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some have postulated that achieving energy balance (or the absence of energy restriction) appears to be important in order to attenuate the effects of the adaptive responses to energy restriction [1,39]. A number of investigations have reported that participants consume less than their weight maintenance energy requirements during refeeding days, and subsequently are in varying degrees of energy restriction for the duration of the intervention [1,6,40,41]. In a comprehensive review on this topic, Sainsbury and colleagues [1] summarized all known randomized controlled trials in overweight/obese adults in which energy balance was intermittently restored.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations have reported that participants consume less than their weight maintenance energy requirements during refeeding days, and subsequently are in varying degrees of energy restriction for the duration of the intervention [1,6,40,41]. In a comprehensive review on this topic, Sainsbury and colleagues [1] summarized all known randomized controlled trials in overweight/obese adults in which energy balance was intermittently restored. Of these five investigations, two resulted in greater weight loss in the intermittent energy restriction than in the continuous energy restriction [9,42] and the three others reported that weight loss was comparable between intermittent energy restriction and continuous energy restriction [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All concepts of intermittent fasting described here, however, have in common a reduced calorie intake on certain days. Altogether, successful intervention studies are available for these fasting forms, which confirm their effectiveness (6). However, a certain degree of willpower and discipline is required for a consistent performance.…”
Section: Introductionmentioning
confidence: 92%